La figura de César en las tragedias españolas del siglo XIX - Martín Puente, Cristina (Cuadernos de Filología Clásica. Estudios Latinos, 2003)
The circumstances around Julius Cesar’ murder are the plot of several Spanish tragedies of the XIXth century: Julio César by José María Díaz, La muerte de César by Ventura de la Vega, La muerte de César by José María Díaz and ¡Bruto! by Tomás Rodríguez Alenza. Also in Catilina José María Díaz makes a moral portrait of Cesar. This paper compares the treatment of the character in each of the pieces and the interpretation of the conspiracy reasons and consequences.